3D Nanostructured Molybdenum Diselenide/Graphene Foam as Anodes for Long-Cycle Life Lithium-ion Batteries. (10th September 2015) - Yao, Jianyu; Liu, Borui; Ozden, Sehmus; Wu, Jingjie; Yang, Shubin; Rodrigues, Marco-Tulio F.; Kalaga, Kaushik; Dong, Pei; Xiao, Peng; Zhang, Yunhuai; Vajtai, Robert; Ajayan, Pulickel M.
Abstract: A self-assembled MoSe2 nanolayers/reduced graphene oxide (MoSe2 /rGO) foam was prepared using a hydrothermal method. The samples were systematically investigated by X-ray diffraction, field emission scanning electron microscopy, energy dispersive X-ray spectroscopy, and high-resolution transmission electron microscopy. Electrochemical performances were evaluated in two-electrode cells versus metallic lithium. It is demonstrated that the obtained MoSe2 /rGO nanocomposites show three-dimensional architecture and excellent electrochemical performance as anode materials for Li-ion batteries. The specific capacity of MoSe2 /rGO anode can reach up to 650 mAh g −1 at a current rate of 0.1C in the voltage range 0.01–3.0 V (vs. Li/Li + ), which is higher than the theoretical capacity of MoSe2 (422 mAh g −1 ). Additionally, the fabricated half cells have shown good rate capability and long cycling stability with 10.9% capacity loss after 600 cycles under a current density of 0.5C. The excellent performance of the synthesized MoSe2 /rGO is attributed to its unique nanostructure, including nanolayered MoSe2, highly conductive rGO networks and mechanically stable 3D architecture.